Intracorporal suturing - driving license necessary? - Romero, Philipp; Nickel, Felix; Müller, Beat P.; Günther, Patrick; Holland-Cunz, Stefan (Journal of pediatric surgery, 2014)
Background - Intracorporeal suturing and knot tying (ICKT) in minimal invasive surgery (MIS) represents a key skill for advanced procedures. Different methods exist for measuring knot quality and performance, but the heterogeneity of these methods makes direct comparisons difficult. The aim of this study is to compare the quality of a laparoscopic knot to one that is performed open. - Methods - To compare open and laparoscopic knot-tying methods we used a surgeon's square knot. For laparoscopic knot tying we used a Pelvitrainer. The 32 participants were divided among 4 groups of different skill levels. Group 1 consisted of 6 senior physicians. Group 2 was made up of 10 first to fourth year interns. Groups 3 and 4 contained 16 medical students who had never performed either laparoscopic procedures or open sutures before. Group 3 participants received a 1-hour hands-on training in suturing, whereas group 4 participants received no prior training. Total time, knot quality, suture placement accuracy, and performance defined the parameters for assessment in this study. - Results - All participants, irrespective of education level were inferior in ICKT compared to open suturing. Only Group 1 showed no significant difference in knot quality and accuracy between the open and laparoscopic suture performance. - Conclusion - It is well documented that psychomotor skills need to be developed before more advanced skills can be put into practice. Training centres for minimally invasive surgery should be an integral part of surgical education. The variables in our study are meaningful and easy to implement. They can be used to measure personal progress and as objective parameters in the development of laparoscopic trainee education.
Available online 30 December 2013
Gesehen am 29.09.2020